(untitled) (Journal of Pathology of Nepal, 2015)
Inflammatory bowel disease is a group of inflammatory disorders of unknown etiology. Various genetic factors, mucosal immune response, inappropriate activation of immune system driven by the presence of various luminal flora and epithelial defects have been postulated. Crohn disease and Ulcerative colitis are the two most common inflammatory bowel diseases. Since, specific clinical laboratory features are lacking which may help in establishing a diagnosis histopathological diagnosis remains the gold standard. This review highlights the known hypothesis regarding the etiopathogenesis of these two diseases and also describes pertinent histological features. Journal of Pathology of Nepal (2015) Vol. 5, 756-765